DEGRADASI LAHAN PADA KEBUN CAMPURAN DAN TEGALAN DI KABUPATEN DHARMASRAYA - Syafrimen Yasin; Gusnidar Gusnidar; Dedy Iskandar (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
A research conducted in Sungai Rumbai, Dharmasraya Regency and in Soil Laboratory Andalas university was aimed to evaluate soil fertility status on the depth below 0-20 cm from several land use types , especially under Mixed Garden and annual cultivated dryland soil. Soil samples were taken on Ultisol at 0-8% slope (late-waving soil surface). Land use types evaluated were forest, annual cultivated dryland, bush land, rangeland covered by Imperata cylindrica and mixed garden. Composite soil samples for soil chemical analysis were taken on the 0-20 cm soil depth with four replications, and 5 drillings for each replication. Undisturbed soil samples by using sample ring were used to analyze sol bulk volume. The data resulted were compared to the criteria and were statistically tested using Analysis of Variance and then were continued by LSD at 5% level. From the results of analyses could be concluded that land use for mixed garden had the higher Organic Carbon (OC) content and the lower bulk volume (BV) than those for annual cultivated dryland soil.Key Words: Degradasi Lahan, Kebun Campuran, Tegalan